2004
DOI: 10.1152/physrev.00045.2003
|View full text |Cite
|
Sign up to set email alerts
|

Renal Vacuolar H+-ATPase

Abstract: Vacuolar H+-ATPases are ubiquitous multisubunit complexes mediating the ATP-dependent transport of protons. In addition to their role in acidifying the lumen of various intracellular organelles, vacuolar H+-ATPases fulfill special tasks in the kidney. Vacuolar H+-ATPases are expressed in the plasma membrane in the kidney almost along the entire length of the nephron with apical and/or basolateral localization patterns. In the proximal tubule, a high number of vacuolar H+-ATPases are also found in endosomes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
476
2
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(501 citation statements)
references
References 554 publications
(439 reference statements)
6
476
2
12
Order By: Relevance
“…Zebrafish HR cells specifically express apical H + -ATPase and NHE as do mammalian renal proximal tubular cells (Yan et al, 2007), which are responsible for about 70% of sodium and 80% of bicarbonate reabsorption in mammalian nephrons (Wagner et al, 2004). As HR cells were demonstrated to have similar functions of acid-base regulation and Na + uptake, they should also express carbonic anhydrases (CAs) and the basolateral H + -HCO 3 + cotransporter (NBC) to fulfill the transepithelial transport mechanisms, as do proximal tubular cells.…”
Section: Membrane-associated and Cytosolic Carbonic Anhydrasesmentioning
confidence: 99%
“…Zebrafish HR cells specifically express apical H + -ATPase and NHE as do mammalian renal proximal tubular cells (Yan et al, 2007), which are responsible for about 70% of sodium and 80% of bicarbonate reabsorption in mammalian nephrons (Wagner et al, 2004). As HR cells were demonstrated to have similar functions of acid-base regulation and Na + uptake, they should also express carbonic anhydrases (CAs) and the basolateral H + -HCO 3 + cotransporter (NBC) to fulfill the transepithelial transport mechanisms, as do proximal tubular cells.…”
Section: Membrane-associated and Cytosolic Carbonic Anhydrasesmentioning
confidence: 99%
“…V-type H + -ATPases are multi-subunit protein complex consisting of at least 14 subunits in humans (for a detailed review on H + -ATPase structure, function, and regulation, see recent reviews: (54,55,119,122,202)). Most subunits occur in different isoforms that may be specific to organs, cell types, or subcellular organelles.…”
Section: The Major Transport Proteins H-atpasesmentioning
confidence: 99%
“…The v-H + -ATPase and its associated protein, (P)RR, are predominantly expressed at the apical surface of the collecting duct where it functions to expel protons into the tubular lumen, thereby contributing to urinary acidification. 126 The findings that the collecting duct is a key site of local RAS activity, where renin is produced in abundance by collecting duct principal cells 127 suggest an Ang-IIdependent activation of the collecting duct v-H + -ATPase and modulation of urinary acidification. 128,129 In agreement with these results, Advani et al 113 concluded that the (P)RR has a primary role in distal nephron proton transport, which at least in part, an Ang-II-dependent phenomenon.…”
Section: The Cross-talk: (P)rrs and Wnt/fz Signaling Systemmentioning
confidence: 99%